1999
DOI: 10.1111/j.1755-6686.1999.tb00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Results of a national epidemiological investigation of HCV infection in dialysis patients

Abstract: Summary The Italian Branch of EDTNA/ERCA organised a national, epidemiological, retrospective study to collect data and implement preventative measures for the spread of HCV infection in dialysis units. A questionnaire was sent to staff in 830 dialysis centres to collect information relating to 1996. Data are presented on incidence/prevalence of HCV infection, antibodies, viraemia and mortality, and comparison of the management of HCV between centres. At variance with the recommendations of the Official Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 4 publications
0
13
0
1
Order By: Relevance
“…17 The small but definite incidence of acute HCV infection detected in chronic HD patients in developed countries, after the elimination of post-transfusion HCV infection, also supports HCV transmission by nosocomial routes. 12,13,18 Several mechanisms could potentially contribute to nosocomial HCV transmission between hemodialysis patients: dialyzer reuse, internal contamination of hemodialysis machines, and contamination of the hands of staff members or of items shared between patients. The relationship between dialyzer reuse and anti-HCV positivity has been confirmed in some 19 but not all studies.…”
Section: Transmission Of Hcv Within Hemodialysis Unitsmentioning
confidence: 99%
“…17 The small but definite incidence of acute HCV infection detected in chronic HD patients in developed countries, after the elimination of post-transfusion HCV infection, also supports HCV transmission by nosocomial routes. 12,13,18 Several mechanisms could potentially contribute to nosocomial HCV transmission between hemodialysis patients: dialyzer reuse, internal contamination of hemodialysis machines, and contamination of the hands of staff members or of items shared between patients. The relationship between dialyzer reuse and anti-HCV positivity has been confirmed in some 19 but not all studies.…”
Section: Transmission Of Hcv Within Hemodialysis Unitsmentioning
confidence: 99%
“…The reported prevalence of hepatitis C virus (HCV) infection ranges from 8 to 20% in dialysis patients receiving maintenance dialysis in the developed world; [1][2][3][4][5] the frequency of HCV is much higher in patients undergoing dialysis in less-developed countries. [6][7][8][9][10][11][12][13][14] Recent studies have shown that HCV is an important cause of morbidity and mortality in chronic dialysis patients.…”
Section: Introductionmentioning
confidence: 99%
“…Their number was significantly higher in the HCV positive group. It is a result opposite to what was reported in the literature, especially in the DOPPS study, prevalence and risk of seroconversion were lower in dialysis units with a large number of experienced nurses [32][33][34][35][36]. This result could be explained by the lack of training for experienced nurses leading to a relaxation of the application of universal rules of hygiene, even if a correlation was found between the number of chronic hemodialysis and the number of nurses Experienced (correlation coefficient 0.54, p=0.03).…”
Section: Factors Prevalence Of Hepatitis C Virus In Hemodialysismentioning
confidence: 86%